Ferroptosis-Associated Molecular Features to Aid Patient Clinical Prognosis and Therapy Across Human Cancers - Cui, Kaisa; Gong, Liang; Wang, Kang; Wang, Yuanben; Huang, Liuying; Liu, Bingxin; Li, Qilin; Zhang, Qiang; Fei, Bojian; Huang, Zhaohui (Frontiers in Immunology, 2022)
Ferroptosis is a new non-apoptotic form that regulates cell death and is mainly dependent on iron-mediated oxidative damage and subsequent cell membrane damage. Ferroptosis may be a potential therapeutic strategy for immunotherapy, chemotherapy, and radiotherapy in human cancers. Numerous studies have analyzed ferroptosis-correlated signatures or genes, but a systematic landscape of associations among tumor ferroptosis, clinical outcomes, tumor microenvironment, and therapies in human cancers is lacking. Here, we developed a relative ferroptosis level (RFL) combined with drive/suppress regulators and validated it in the Gene Expression Omnibus datasets of ferroptotic drug treatment. Based on this effective evaluation method, we classified about 7,000 tumor samples into high and low RFL groups in each cancer type and observed that high RFL cases demonstrate favorable survival outcomes in nine cancer types from The Cancer Genome Atlas. Then, several RFL-correlated candidate genes that have not been reported to be ferroptosis-related were selected and experimentally validated in five cancer cell lines using Erastin treatment. We further showed that both immunostimulatory and immunosuppressive phenotypes were observed in high RFL tumors, suggesting that the consideration of ferroptosis could be a potential strategy in cancer immunotherapy. Moreover, we found that high RFL cases/cells showed responder or sensitivity to chemotherapy and radiotherapy. Our study provides a comprehensive molecular-level understanding of ferroptosis and may have practical implications for clinical cancer therapies, including immunotherapy, chemotherapy, and radiotherapy.